IL-17 can be protective or deleterious in murine pneumococcal pneumonia. - Neil D Ritchie; Ryan Ritchie; Hannah K Bayes; Tim J Mitchell; Tom J Evans (PLoS Pathogens)
Streptococcus pneumoniae is the major bacterial cause of community-acquired pneumonia, and the leading agent of childhood pneumonia deaths worldwide. Nasal colonization is an essential step prior to infection. The cytokine IL-17 protects against such colonization and vaccines that enhance IL-17 responses to pneumococcal colonization are being developed. The role of IL-17 in host defence against pneumonia is not known. To address this issue, we have utilized a murine model of pneumococcal pneumonia in which the gene for the IL-17 cytokine family receptor, Il17ra, has been inactivated. Using this model, we show that IL-17 produced predominantly from γδ T cells protects mice against death from the invasive TIGR4 strain (serotype 4) which expresses a relatively thin capsule. However, in pneumonia produced by two heavily encapsulated strains with low invasive potential (serotypes 3 and 6B), IL-17 significantly enhanced mortality. Neutrophil uptake and killing of the serotype 3 strain was significantly impaired compared to the serotype 4 strain and depletion of neutrophils with antibody enhanced survival of mice infected with the highly encapsulated SRL1 strain. These data strongly suggest that IL-17 mediated neutrophil recruitment to the lungs clears infection from the invasive TIGR4 strain but that lung neutrophils exacerbate disease caused by the highly encapsulated pneumococcal strains. Thus, whilst augmenting IL-17 immune responses against pneumococci may decrease nasal colonization, this may worsen outcome during pneumonia caused by some strains.